(untitled) (Journal of Organizational Psychology, 2023)
The oil and gas sector in Middle East is facing many challenges regarding employee turnover especially in (DLPS) company. Employee turnover leads to reduce the employee’s performance and productivity. Moreover, employee turnover also affects the organizational performance in general. High rates of employees’ turnover cause many challenges to the organizations. Employee turnover has escalated to 14.2% in 2018 (DPLS, 2018). Likewise, many companies keep long service and loyal) employees intact while there are also other types of employees who leave their organization. The main idea behind choosing this topic is to address the reasons that cause the high rate of employees’ turnover and how to solve the issue. Moreover, the researcher aimed to investigate in depth the concept of how reward system and training could improve employee retention. To make this action researcher done, the researcher gathered data in questionnaire form (30 questionnaires) from previous and existed employees at DLPS Company and made five (5) interviews with departments managers to get valid data to build the study on. The results showed that, most of the targeted sample were not satisfied about their wages and the working time. In addition, due to the analysis of the quantitative and qualitative data, there is positive relationship between the hypotheses and the high rate of employees’ turnover.